Upaya Meningkatkan Hasil Belajar IPS Peserta Didik dengan Menggunakan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (STST) pada Kelas VII-B MTS Miftahul Jannah Palangka Raya - Astinah Astinah; Muhamad Ramli (Neraca: Jurnal Pendidikan Ekonomi, 2018)
This study shows outcomes of social studies students. The method is to use the Classroom Action Research (CAR) design. Subjects needed for class VII-B MTs MifTahul Jannah Palangka Raya, which numbered 23 students, for the data collection techniques used were observation and tests. While this study uses qualitative and quantitative data analysis. The results of the survey show that: (1) There is an increase in learning outcomes. This is known as the initial stage with an average value of 64 with classical completeness. This is the first cycle which reached an average of 72 with the artistic integrity of 56.52% and the results achieved by students in this second cycle of These values indicate that learning using the average cost of 86.95% in class VII-B MTs Miftahul Jannah Palangka Raya